Trend Analysis of Fahion Dress Patterns of Female Students - Komalasari, Novi; Sutarman, Sutarman; Rahman, Arif (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The development of fashion trends in the modern era has caused considerable changes in people's clothing styles, including among students. Students in Islamic universities not only follow the development of popular fashion, but are also faced with the demand to maintain the principle of dressing in accordance with Islamic values. This research aims to analyze fashion trends on the dress patterns of female students of the Faculty of Islamic Religion, Ahmad Dahlan University and understand how female students interpret the concept of dressing according to shari'a in daily life in the campus environment. This study uses a qualitative approach with the research subject, namely a student of the Faculty of Islamic Religion, Ahmad Dahlan University. Data collection techniques are carried out through interviews, observations, and documentation, while data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that fashion trends have a significant cause for the dress patterns of female students, especially through the role of social media which is a source of reference for clothing styles. However, most of the female students still try to adapt their style of dress to the principles of sharia dress in accordance with the values of modesty in Islam.